2018
DOI: 10.14639/0392-100x-1694
|View full text |Cite
|
Sign up to set email alerts
|

Bone-anchored hearing implant surgery: our experience with linear incision and punch techniques

Abstract: Bone-anchored hearing implant surgery: our experience with linear incision and punch techniques La chirurgia delle protesi acustiche ancorate all'osso: la nostra esperienza con le tecniche con incisione lineare e con punch

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In addition, the reported mean surgical time for MIPS in a multicentre study was 16 mins 17 . The impressive reduction of surgical time of MIPS compared with other surgical procedures makes this technique more suitable for local anaesthesia and more cost effective 22 , 23 . Furthermore, Sardiwalla et al investigated patient satisfaction using a Surgical Satisfaction Questionnaire (SSQ-8) modified for MIPS and found that patient experiences with MIPS were overwhelmingly positive.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reported mean surgical time for MIPS in a multicentre study was 16 mins 17 . The impressive reduction of surgical time of MIPS compared with other surgical procedures makes this technique more suitable for local anaesthesia and more cost effective 22 , 23 . Furthermore, Sardiwalla et al investigated patient satisfaction using a Surgical Satisfaction Questionnaire (SSQ-8) modified for MIPS and found that patient experiences with MIPS were overwhelmingly positive.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there was an implant survival rate of >95% at the 20-week follow-up (26). Subsequent studies comparing the MIPS technique to the LITT-P showed similar favorable outcomes, even with longer follow-up, regarding soft tissue reactions (27)(28)(29)(30)(31)(32)(33). Moreover, a shorter surgical time (27)(28)(29)(30)(31)(32)(33), better cosmetic appearance (28,29), and improved sensibility (28) were reported in favor of the MIPS technique compared with the LITT-P approach.…”
Section: Introductionmentioning
confidence: 92%
“…Nowadays, the less invasive linear incision technique with tissue preservation (LITT-P) is advocated based on similar or less (adverse) soft tissue reactions (10)(11)(12)(13)(14)(15)(16) as well as favorable outcomes in surgical time, cosmetics, and numbness (15)(16)(17)(18)(19)(20)(21). Recently, minimally invasive punch-only techniques have been introduced to reduce soft tissue trauma (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). A standardized approach was developed by Oticon Medical AB (Askim, Sweden): the minimally invasive Ponto surgery (MIPS) (26).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing benefits to patients, improvements in clinical efficiency using MIPS have been reported in cost analysis studies ( 32 ). While several studies have reported comparable implant survival rates for MIPS compared to LITT-P ( 27 29 , 31 , 33 ), lower implant survival for MIPS has also been reported ( 25 , 26 , 34 ). Possible reasons can be the reduced visibility during the procedure, introducing a potential risk of angulated insertion or interposing soft tissue.…”
Section: Introductionmentioning
confidence: 96%